2007
DOI: 10.1638/1042-7260(2007)038[0363:srtacc]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Serologic Response to a Canarypox-Vectored Canine Distemper Virus Vaccine in the Giant Panda (Ailuropoda Melanoleuca)

Abstract: The giant panda (Ailuropoda melanoleuca) is known to be susceptible to natural infection with canine distemper virus (CDV). Vaccination of giant pandas with conventional modified live CDV vaccines has been avoided due to the numerous carnivore species known to have become infected with CDV after vaccination. Serum-neutralizing antibodies to CDV were measured after s.c. and i.m. annual vaccination with a canarypox-vectored recombinant CDV vaccine in an adult male and female giant panda over the period of 2 yr. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 2 publications
0
20
0
Order By: Relevance
“…For those species, different vaccine approaches have been evaluated, including DNA vaccines [78], non-replication competent and replication-competent vector vaccines [79,80], as well as rationally attenuated vaccines [81,82]. A CDV F and H protein-expressing canarypox-based vaccine has been licensed for several years now, and has been successfully used in various wildlife species [83,84]. In addition, these studies have significantly contributed to our understanding of morbillivirus correlates of protection and the role of maternal immunity.…”
Section: Vaccine and Drug Developmentmentioning
confidence: 99%
“…For those species, different vaccine approaches have been evaluated, including DNA vaccines [78], non-replication competent and replication-competent vector vaccines [79,80], as well as rationally attenuated vaccines [81,82]. A CDV F and H protein-expressing canarypox-based vaccine has been licensed for several years now, and has been successfully used in various wildlife species [83,84]. In addition, these studies have significantly contributed to our understanding of morbillivirus correlates of protection and the role of maternal immunity.…”
Section: Vaccine and Drug Developmentmentioning
confidence: 99%
“…Canarypox-vectored vaccines, developed for use in domestic canines, are incapable of replicating in the host cell, but can elicit an appropriate host immune response [137][138][139]. The canarypox-vectored vaccine has proven to be effective in challenge studies in various wildlife species including European ferrets (M. putorius furo), giant panda (A. melanoleuca), fennec foxes (V. zerda), meerkats (Suricata suricatta) and Siberian polecats (Mustela eversmanni) [140][141][142][143]. A more recent study on vaccine efficiency in tigers (P. tigris) found that both the live attenuated and the recombinant canarypox-vectored vaccine appeared safe for use, although the live attenuated vaccine produced a significantly stronger and more consistent immune response in the tigers [144].…”
Section: Treatment and Controlmentioning
confidence: 99%
“…Canine distemper virus (CDV) (family Paramyxoviridae ) is an enveloped, nonsegmented, single-stranded, negative-sense RNA virus responsible for the disease canine distemper (CD), which has a high mortality rate in domestic and wild carnivore hosts (13). Vaccination has proven to be an effective intervention strategy against CDV in domestic hosts (3, 4); however, there is still a lack of quantitative data on the effects of a CDV vaccine in wildlife (5).…”
Section: Genome Announcementmentioning
confidence: 99%
“…Vaccination has proven to be an effective intervention strategy against CDV in domestic hosts (3, 4); however, there is still a lack of quantitative data on the effects of a CDV vaccine in wildlife (5). …”
Section: Genome Announcementmentioning
confidence: 99%